Factors associated to non adherence to antirretroviral treatment in adults above 50 years old who have HIV/aids - Padoin, Stela Maris M; Paula, Cristiane C de; Zuge, Samuel S; Primeira, Marcelo R; Santos, Érika Éberline P; Tolentino, Lidiane C (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: drug technology implied on morbidity and mortality reduction of people who have HIV/aids. Levels of adherence to antiretroviral use influences on treatment’s success or not. Adherence is considered as the biggest determinant as therapeutic response, however there’s not a standard method established for its evaluation. Objective: to identify factors associated to the non-adherence to antiretroviral treatment in adults above 50 years old who have aids. Method: cross-sectional design with a population of 72 patients. Data collection was developed, after ethics committee approval, with structured interview, from April/2009 to October/2010. It was developed bi-varied analysis, crossing the result (adherence to ARVT) with behavioral varies of non-adherence classifications. Results: non-adherence prevalence was of 29,2%. Factors associated to non-adherence were: knowledge about viral load and treatment motive; alcoholic beverage; side effects; coincidence between work time and time to ingest any medicine dose; assistance time in the Service; frequency to consults; and necessity of someone that takes one to the Service. Conclusion: these factors imply on patient’s health and it’s going to be associated on caring for oneself, in order to minimize illness possibilities, and caring for the other, referring to infection transmission potential on collective level.